2019
DOI: 10.1177/2325967119878415
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Mental Health Scores and Achieving Patient Acceptable Symptom State Are Predictive of Return to Work After Arthroscopic Rotator Cuff Repair

Abstract: Background:The incidence of rotator cuff repairs has risen dramatically over the past 10 years, most notably in the working-class population. Return to work (RTW) is a valuable outcome measure to set patient expectations before surgery.Purpose:To establish the rate of RTW after rotator cuff repair with respect to stratified levels of occupational demand (sedentary, light, moderate, and heavy) and to identify clinical factors significantly associated with postoperative RTW.Study Design:Cohort study; Level of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 54 publications
(62 reference statements)
1
29
1
Order By: Relevance
“…In total, 13 studies were included in this review. z All studies were retrospectively performed, consisting of 7 level 4 studies, 1,3,6,14,17,22,29 5 level 3 studies, 11,13,26,30,32 and 1 level 2 study. 2 This search strategy is summarized in Figure 1.…”
Section: Prisma Search Process and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 13 studies were included in this review. z All studies were retrospectively performed, consisting of 7 level 4 studies, 1,3,6,14,17,22,29 5 level 3 studies, 11,13,26,30,32 and 1 level 2 study. 2 This search strategy is summarized in Figure 1.…”
Section: Prisma Search Process and Resultsmentioning
confidence: 99%
“…3,17,26,32 It was found that the workers' compensation group had lower return-to-work rates (50.9%) than the non-workers' compensation group (86%), but the difference only approached significance (P = .089). In addition, Gowd et al 13 and Hawkins et al 14 reported conflicting results, with Gowd et al finding no difference in outcomes between 79 workers' compensation cases and controls, while Hawkins et al noted significantly worse outcomes in their 8 workers' compensation cases. Owing to insufficient detail in work outcome reporting, these 2 studies were not included in meta-analysis.…”
Section: Return To Work By Workers' Compensation Statusmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 9 , 10 In addition, mental health has been shown to be predictive of patient return to work at full duty after rotator cuff surgery. 11 To our knowledge, there has been no study that has analyzed the association of mental health scores and functional outcome scores after distal biceps repair. We hypothesize that low scores on a validated mental health measure are associated with worse patient-reported outcome measures and increased difficulty with return to work and sport.…”
mentioning
confidence: 99%